(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2024)
This article discusses the history of the emergence of homeopathic medicine pioneered by Dr. Burhanuddin al-Helmi during the British colonial period began when he studied in India in 1935 and he continued expanding on it throughout his life till his passing in 1969. However, this homeopathic procedure was less popular among the Malays as they were still practicing traditional Malay and Islamic medication that was interspersed with Quranic verses, as well as modern medicines in hospitals and clinics introduced by the British colonial. This is because homeopathy medicine is still new and has not been widely revealed. This writing will perceive how his education in India has influenced his interest in homeopathic medicine and the development of this medicine in Malaysia. This study was conducted using the qualitative approach by analysing articles written by Dr. Burhanuddin and several other homeopathic researchers and historians. The findings show that Dr. Burhanuddin’s homeopathy was found to be as an alternative medical treatment to allopathy. The article also concludes that the historical development of homeopathy medical science in Malaysia dating back to the 1930s, including the establishment of the Homeopathic Society Federation of Malaya (PHPTM) in 1961, was the efforts and the roles of a Malay nationalist, Dr. Burhanuddin, who was the first homeopathic practitioner of medicine in Malaysia. Makalah ini1 membincangkan sejarah kemunculan perubatan homeopati yang telah dipelopori oleh Dr. Burhanuddin al-Helmi semasa bermulanya zaman pemerintahan British ketika beliau mempelajari ilmu perubatan itu di India pada tahun 1935 sehinggalah pada akhir hayatnya dalam tahun 1969. Namun begitu, perubatan ini kurang popular dalam kalangan masyarakat Melayu tradisional kerana mereka masih mengamalkan amalan perubatan tradisional dan jampi serapah yang diselang-seli dengan ayat-ayat al-Quran, di samping perubatan moden di hospital dan klinik yang diperkenalkan oleh pihak British. Hal ini berlaku disebabkan perubatan homeopati masih baharu dan belum didedahkan secara besar-besaran. Penulisan ini melihat bagaimana pendidikan beliau di India telah mempengaruhi minatnya dalam perubatan homeopati dan perkembangan perubatan ini di Malaysia. Makalah ini hanya menggunakan pendekatan kualitatif melalui kaedah kepustakaan iaitu sumber karya yang ditulis oleh beliau serta pengkaji perubatan homeopati dan sejarawan lain. Dapatan kajian menunjukkan bahawa perubatan homeopati yang diamalkan oleh Dr. Burhanuddin merupakan alternatif rawatan kepada perubatan alopati. Penulisan ini menyimpulkan bahawa sejarah perkembangan ilmu perubatan homeopati di Malaysia yang bertapak sejak dari tahun 1930-an, termasuk penubuhan Persatuan Homeopathy Persekutuan Tanah Melayu (PHPTM) pada tahun 1961, merupakan hasil usaha dan peranan Dr. Burhanuddin, seorang nasionalis Melayu yang juga merupakan pengamal ilmu perubatan homeopati pertama di Malaysia.